Use of the RSA/RCOD index to identify training priority in soccer players - Wong, D. P.; Hjelde, G. H.; Cheng, C.-F.; Ngo, J. K. (The Journal of Strength and Conditioning Research, 2015)
The use of RSA/RCOD index indicates the repeated change-of-direction (RCOD) performance relative to the repeated-sprint ability (RSA) and provides a standardized approach to prioritize training needs for RSA and RCOD. To compare the RSA/RCOD index among different age groups, RSA and RCOD were measured from 20 under-16 players (U16), 20 under-19 players (U19), and 17 first-team professional players (PRO) from a football (soccer) club that has regular participation in the UEFA Champions League. Each player performed the RSA and RCOD tests, during which the fastest time (FT), average time (AT), total time (TT), and percentage decrement score (%Dec) were recorded. No significant differences were found in RSA/RCOD index-FT, AT, TT, and %Dec among the 3 groups (p > 0.05) and between U19 and PRO in all RSA and RCOD measures (p > 0.05). Most values of RSA/RCOD index were 0.51 among the U16, U19, and PRO groups. Moreover, we concluded that the RSA/RCOD index might not be further changed after 16 years of age unless specific training programs for RSA and RCOD are prescribed. Therefore, this study provides an empirical case, and coaches can establish the RSA/RCOD index value relevant to their training system and monitor players' training needs of RSA and RCOD in a longer term.